Soziale Aengste im Kindes-und Jugendalter - Schuch, Bibiana (Array, 2009)
Social anxiety is very common in children and leads to considerable impairment. Some of the biological and psychosocial risks are well known. The analysis of these factors may help to understand the symptomatology for planning preventive and therapeutic interventions.